Is digital inclusion fighting disability stigma? Opportunities, barriers, and recommendations. Issue 5 (8th June 2021) - Tsatsou, Panayiota
Abstract: This paper presents a focus group study of the role of digital inclusion in overcoming disability stigma. It reviews stigma literature and contrasting disability models, ultimately arguing in favor of the value of the biopsychosocial approach to the role of digital inclusion in disability stigma. The paper qualitatively explores the stigma experienced by people with disabilities and the ways in which digital inclusion might affect such experiences. It asserts that the benefits of digital inclusion depend, simultaneously, on bio-medical, social, and personal/psychological levels. In addition, prominent barriers to digital inclusion, such as low accessibility and usability and ineffective technology design, are determined by complex biopsychosocial factors, rather than purely bio-technical or social parameters. Thus, the paper recommends the adoption of the biopsychosocial model of disability, in order digital inclusion research to generate longitudinal insights into the actual and potential role of digital inclusion in people with disabilities' social inclusion and welfare. Points of interest: This is a study of what people with different or similar disabilities think of the role of digital technologies in their experiences of disability stigma. The people with disabilities who participated in the study argued about the positive role that digital technologies play in alleviating: a) medical aspects of their stigma by helping them cope with everyday life tasks; b) social aspects of their stigma by helping them socialise and participate in the society; and c) psychological aspects of their stigma by helping them express freely and be more confident. At the same time, the participants criticised the design of digital technologies and argued that digital design often worsens their experiences of stigma, as it reinforces medical, social and psychological aspects of such stigma. The study recommends that future research on the role of digital technologies in disability stigma should shed light on medical, social and psychological aspects and forces of disability stigma.